Telemedicine-Enabled Otoscopes as Catalysts for Accessible and Preventive Ear Health Care: Systematic Review and Meta-analysis - Girish Chandra Dash; Krushna Chandra Sahoo; Shubhankar Dubey; Rakesh Kumar Sahoo; Jyotsna Naik; Kavitha Rajsekar; Debdutta Bhattacharya; Sanghamitra Pati (Wolters Kluwer Medknow Publications, 2024)
Background: Maintaining optimal hearing health and preventing ear infections is crucial across all life stages, spanning from before birth and infancy to middle age and beyond. The primary aim of the research was to evaluate and compare the effectiveness of the telemedicine-enabled otoscope (TEO) in diagnosing ear diseases with that of the conventional otoscope. Materials and Methods: The databases PubMed, Cochrane, and Embase were thoroughly searched to find original studies on TEO at the community as well as hospital levels along with meta-analysis for comparison with standard diagnostic methods using traditional otoscopes. Results: The telemedicine-equipped otoscope displays a sensitivity of 82% (confidence interval 0.78-0.95) and a specificity of 95% (confidence interval 0.93-0.96). When employed by physicians, the combined sensitivity and specificity become 84% (confidence interval 0.79-0.88) and 91% (confidence interval 0.87-0.94), respectively. Community Health Workers (CHWs) using telemedicine-enabled otoscopes exhibit a collective sensitivity of 80% (confidence interval 0.72-0.87) and a collective specificity of 97% (confidence interval 0.95-0.98). Snapping multiple photographs and removal of cerumen where necessary in increasing the quality of the photographs for diagnosis. Conclusions: The TEO holds the promise of substantially enhancing the accessibility of audiology services, encompassing evaluation, public outreach, and fundamental care. Its implementation has the potential to fortify primary health care environments, contributing to the prevention of ear diseases and assisting in mitigating the shortage of skilled ear care professionals.